Más de un bicentenario entre el guano y el mar - Cárdenas Alayza, Susana (2022)
This essay reviews the history of the management and extraction schemes of two large industries that have evolved along the Peruvian marine ecosystem during the past two hundred years of the nation’s life: guano harvest and Peruvian pilchard industrial fishery. It also provides a current perspective on the effects of climate change on the Humboldt Current System and closes with a general reflection on the lessons learned to face the future of the Peruvian marine ecosystem in a more responsible manner.